2020
DOI: 10.1108/jm2-08-2018-0128
|View full text |Cite
|
Sign up to set email alerts
|

Municipal solid waste management considering NGO’s role in consumer environmental awareness and government regulations for air pollution

Abstract: Purpose The purpose of this study is twofold: first, to examine the role of non-governmental organizations (NGOs) in increasing customer environmental awareness (CEA) to decrease the municipal solid waste (MSW), and secondly, to examine the effect of government policies in the amount of air pollution caused by transfer stations (TSs). Design/methodology/approach This study proposes a mixed-integer nonlinear programming model. For solving this multi-objective problem, the authors use epsilon constraint method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Habila & Bogoro (2021) revealed that in Africa, policy and funding are major issues affecting SWM. Rabbani et al (2020) also confirmed the 'assumption that by allocating budget (funds) to NGOs for increasing Consumer Environmental Awareness (CEA), the produced waste will be decreased. '…”
Section: Comparison Of Ngo Perspectives On Whether or Not Ngo-ngo Par...supporting
confidence: 56%
See 1 more Smart Citation
“…Habila & Bogoro (2021) revealed that in Africa, policy and funding are major issues affecting SWM. Rabbani et al (2020) also confirmed the 'assumption that by allocating budget (funds) to NGOs for increasing Consumer Environmental Awareness (CEA), the produced waste will be decreased. '…”
Section: Comparison Of Ngo Perspectives On Whether or Not Ngo-ngo Par...supporting
confidence: 56%
“…Singh & Dey (2015) working in different municipalities of Nanipur, India found the NGOs that are capable to make remarkable contributions in the management of municipal solid waste and hence recommended the municipal authority to work with NGOs and other local civic bodies in managing the solid waste problem in the municipality. Study by Rabbani et al (2020) confirmed to be true the 'assumption that by allocating budget (funds) to NGOs for increasing consumer environmental awareness (CEA), the produced waste will be decreased. Similarly, a study in Shanghai by Arantes et al (2020) revealed that NGOs are very effective intermediaries between state and society in promoting environmental governance practices, and that a collaborative governance model can enhance public participation in waste classification, among other things, in urban areas.…”
Section: Introductionmentioning
confidence: 92%
“…Govind Kharat et al [74] proposed a fuzzy Delphi method (FDM) to obtain the critical factors obtained from expert groups working in the field of WM for the evaluation of technology alternatives. Rabbani et al [71] examined the role of nongovernmental organizations (NGOs) in increasing customer environmental awareness (CEA) to decrease MSW. Thus, a noticeable pattern from this collection of papers is the use of MADM methods to define criteria and collect stakeholders' preferences, a feature that is complicated to achieve when only using MODM methods, making the combination of methods an attractive approach.…”
Section: Combinations Of Methodsmentioning
confidence: 99%
“…Governments have the capability to improve air quality through policy change [24]. The COVID-19 pandemic reveals just how seriously governments take their responsibility to ensure the health and well-being of the populations they govern [25], and restricting activity to limit pathogen spread can have other public health repercussions, such as reducing air pollution levels [26]. Social media is a useful tool for collecting data about public opinion and conducting analysis of air pollution.…”
Section: Urban Air Pollution and Public Environmental Concerns Have A...mentioning
confidence: 99%